Effects of Comorbid Fibromyalgia Syndrome on activities of daily living in multiple sclerosis patients - ULUSOY, Ersin Kasım (Arquivos de Neuro-Psiquiatria, 2020)
Objective: To investigate the frequency of Comorbid Fibromyalgia Syndrome and its effects on quality of life and activities of daily living without any known psychiatric problem (schizophrenia or bipolar disorder) or severe disability, other than depression, in patients with multiple sclerosis, which is known to be a chronic disease in young adults. Methods: The study included 103 patients diagnosed with multiple sclerosis, following McDonald criteria, who had relapsing remitting disease. The Fibromyalgia Impact Questionnaire, Beck Anxiety Inventory, Beck Depression Inventory, Pittsburgh Sleep Quality Index, Fatigue Severity Scale, and Multiple Sclerosis Quality of Life-54 were applied for all patients. Results were analyzed using statistical methods. Results: Mean age was 35.04±8.72 years in the study population. The Expanded Disability Status Scale (EDSS) score was 2.21±0.93. Comorbid Fibromyalgia Syndrome was detected in 20 patients (19.4%). The mean score of Multiple Sclerosis Quality of Life-54 was found to be significantly higher in multiple sclerosis patients with Comorbid Fibromyalgia Syndrome when compared to those without it (34.80±9.14 versus 71.67±13.95; p<0.05). Conclusion: These results indicate that increased frequency of Comorbid Fibromyalgia Syndrome in multiple sclerosis causes worsening in activities of daily living and quality of life, delayed diagnosis, disability progression, and increased admission rates. Questioning and appropriately managing Comorbid Fibromyalgia Syndrome in clinical practice are important to improve the quality of life in multiple sclerosis patients.
Keywords: Fibromyalgia; Quality of Life; Activities of Daily Living; Fatigue